Feasibility, safety, clinical, and laboratory effects of convalescent plasma therapy for patients with Middle East respiratory syndrome coronavirus infection: a study protocol - Arabi, Y; Balkhy, H; Hajeer, A; Bouchama, A; Hayden, F; Al-Omari, A; Al-Hameed, F; Taha, Y; Shindo, N; Whitehead, J; Merson, L; AlJohani, S; et al. (SpringerPlus, 2015)
As of September 30, 2015, a total of 1589 laboratory-confirmed cases of infection with the Middle East respiratory syndrome coronavirus (MERS-CoV) have been reported to the World Health Organization (WHO). At present there is no effective specific therapy against MERS-CoV. The use of convalescent plasma (CP) has been suggested as a potential therapy based on existing evidence from other viral infections. We aim to study the feasibility of CP therapy as well as its safety and clinical and laboratory effects in critically ill patients with MERS-CoV infection. We will also examine the pharmacokinetics of the MERS-CoV antibody response and viral load over the course of MERS-CoV infection. This study will inform a future randomized controlled trial that will examine the efficacy of CP therapy for MERS-CoV infection. In the CP collection phase, potential donors will be tested by the enzyme linked immunosorbent assay (ELISA) and the indirect fluorescent antibody (IFA) techniques for the presence of anti-MERS-CoV antibodies. Subjects with anti-MERS-CoV IFA titer of ≥1:160 and no clinical or laboratory evidence of MERS-CoV infection will be screened for eligibility for plasma donation according to standard donation criteria. In the CP therapy phase, 20 consecutive critically ill patients admitted to intensive care unit with laboratory-confirmed MERS-CoV infection will be enrolled and each will receive 2 units of CP. Post enrollment, patients will be followed for clinical and laboratory outcomes that include anti-MERS-CoV antibodies and viral load. This protocol was developed collaboratively by King Abdullah International Medical Research Center (KAIMRC), Gulf Cooperation Council (GCC) Infection Control Center Group and the World Health Organization-International Severe Acute Respiratory and Emerging Infection Consortium (ISARIC-WHO) MERS-CoV Working Group. It was approved in June 2014 by the Ministry of the National Guard Health Affairs Institutional Review Board (IRB). A data safety monitoring board (DSMB) was formulated. The study is registered at http://www.clinicaltrials.gov (NCT02190799).